RELEVANSI NILAI SUSTAINABILITY REPORTING: BUKTI EMPIRIS INDONESIA - Susi Retna Cahyaningtyas; Saipul Arni Muhsyaf; Rahmi Sri Ramadhani; Zuhrotul Isnaini (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
This study empirically examines the value relevance of sustainability reporting (SR) in explaining the market value of the firm. The sample of this study is all non-bank companies and financial institutions that go public on the Indonesia Stock Exchange which disclose sustainability reporting for the period 2010 - 2020. Based on these conditions, 590 observations were obtained. Hypothesis testing using SPSS. If the SR*EPS (Earning Per Share) interaction and the SR*BVPS (Book Value Per Share) interaction are significantly positive on the market value, then SR has a value relevance in explaining the company's market value. The results show that SR reduces value relevance. This result indirectly proves that the company's financial information can still be used as a basis for decision-making by investors.